Low-Field Magnetic Resonance Imaging: A New Generation of Breakthrough Technology in Clinical Imaging - Heiß, Rafael; Nagel, Armin Michael; Laun, Frederik Bernd; Uder, Michael; Bickelhaupt, Sebastian (Investigative Radiology, 2021)
ABSTRACT: Magnetic resonance imaging (MRI) plays a pivotal role in diagnostic imaging. In today's clinical environment, scanners with field strengths of 1.5 to 3 T are most commonly used. However, recent technological advancements might help to augment the clinical usage and availability of MRI via the introduction of high-performance low-field MRI systems (ranging from 0.1-0.55 T in current systems). The combination of low field strength and high-performance hardware is characterized by increased flexibility, excellent quality of results, and reduced cost. This review discusses the multifaceted potential advantages of a new generation of high-performance low-field MRI systems and presents the potential impact of such systems in terms of socioeconomic benefits as well as positive effects on patient care.
CRIS-Team Scopus Importer:2021-11-05